(untitled) (BEOIBERISTIKA - Časopis za iberijske, latinoameričke i komparativne studije (ISSN: 2560-4163 Online), 2020)
The purpose of this work –which has both a theoretical and a practical nature– is to reflect on some considerations which should be taken into account by the teacher of Spanish as a foreign language when facing the challenge of teaching Spanish phraseology to non-native speakers of Spanish. Keywords: phraseology, phraseological units, SFL teaching-learning.